Case report: Triple-negative breast cancer with low tumour-infiltrating lymphocytes infiltration and good prognosis: a case of Tall Cell Carcinoma with Reversed Polarity and review of the literature - Jiao, Shuoying; Chen, Junpeng; Shen, Jiumei; Peng, Ajing; Chen, Ruifu; Lai, Baoyong; Luo, Chunhua; Fan, Yingyi (Frontiers in Oncology, 2024)
BackgroundTriple-negative breast cancer (TNBC) is a great challenge for clinical management due to the high rate of metastatic recurrence and lack of recognised therapeutic targets, while tumour-infiltrating lymphocytes (TILs) infiltration in TNBC has been discovery provides an opportunity for immunotherapy, and studies have suggested that the level of TILs infiltration is positively correlated with TNBC survival. We found a rare case of TNBC with low TILs infiltration but good prognosis, named Tall Cell Carcinoma with Reversed Polarity (TCCRP), and we investigated it from the perspective of TILs infiltration in order to improve the clinical data of TCCRP.Case presentationa 54-year-old woman with a left breast mass, breast ultrasound showed BI-RADS IVb, puncture diagnosis of invasive ductal carcinoma, postoperative pathology showed papillary structure, cubic and high columnar arrangement of cells, nuclei far away from the base, interstitial fibroplasia, diagnosed as TCCRP. Immunohistochemistry revealed that the tumours were triple-negative breast cancer (negative for ER, PR, and HER-2), with a low Ki-67 proliferation index. TILs were < 10%, with a small infiltration of CD4+ and CD8+ T lymphocytes, positive expression of SMA and FAP, and IDH2, PIK3CA gene mutation. The patient underwent postoperative chemotherapy, 11 months follow-up, no recurrence and metastasis.ConclusionTCCRP is a rare TNBC with inert biological behaviours and good prognosis. We found low infiltration of TILs in the pathological tissue of this case, which may be a characteristic of TCCRP, and the presence of Cancer-Associated Fibroblasts (CAF) in the interstitium of the tumour in this case may have suppressed the anti-tumour immunity to some extent, and further studies on the immune characteristics of the tumour microenvironment (TME) in TCCRP are needed.